2008
DOI: 10.1126/science.1160342
|View full text |Cite
|
Sign up to set email alerts
|

A Global View of Gene Activity and Alternative Splicing by Deep Sequencing of the Human Transcriptome

Abstract: The functional complexity of the human transcriptome is not yet fully elucidated. We report a high-throughput sequence of the human transcriptome from a human embryonic kidney and a B cell line. We used shotgun sequencing of transcripts to generate randomly distributed reads. Of these, 50% mapped to unique genomic locations, of which 80% corresponded to known exons. We found that 66% of the polyadenylated transcriptome mapped to known genes and 34% to nonannotated genomic regions. On the basis of known transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
858
9
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,143 publications
(918 citation statements)
references
References 29 publications
37
858
9
14
Order By: Relevance
“…Depth requirements: The first RNA-seq studies in mammals were performed on the polyadenylated fraction of cellular transcripts and the resulting libraries were sequenced to ~10-50 M reads (Mortazavi et al, 2008;Sultan et al, 2008). The first studies in prokaryotes reported the sequencing of rRNA-depleted samples to ~1-7 M reads/library (Oliver et al, 2009;Perkins et al, 2009;Yoder-Himes et al, 2009).…”
Section: Strand-specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Depth requirements: The first RNA-seq studies in mammals were performed on the polyadenylated fraction of cellular transcripts and the resulting libraries were sequenced to ~10-50 M reads (Mortazavi et al, 2008;Sultan et al, 2008). The first studies in prokaryotes reported the sequencing of rRNA-depleted samples to ~1-7 M reads/library (Oliver et al, 2009;Perkins et al, 2009;Yoder-Himes et al, 2009).…”
Section: Strand-specificitymentioning
confidence: 99%
“…In 2008 the first studies reported RNA-seq-based transcriptomics for murine (Mortazavi et al, 2008) and human cells (Sultan et al, 2008), and thus for potential host organisms of bacterial infections. These early studies focused on coding gene expression as reverse transcription was primed using oligo(dT) primers to selectively sequence only polyadenylated transcripts (mRNAs or polyadenylated lncRNAs).…”
Section: Strand-specificitymentioning
confidence: 99%
“…In contrast, although the third dataset enables us to explore the selection pressure that works exclusively on 5'UTRs, only a small proportion of transcripts with biased properties can be included in the analysis. These transcripts tend to be the products of the genes with short 5'UTR, genes that are lowly expressed, or genes not alternatively spliced, although > 90% of human genes have multiple isoforms [23]. Given the distinct properties of selected transcripts in the three datasets, we reason that if our hypothesis is correct, all three datasets will yield consistent results.…”
Section: Resultsmentioning
confidence: 97%
“…80 Using this technology, investigators have sequenced the entire genome for selected subsets of human cells, including malignant blasts from an AML patient with normal cytogenetics. 81,82 These cutting edge technologies have rapidly advanced our understanding of how genomic changes impact expression, identifying thousands of new polymorphisms and promoter loci. 78,83,84 Currently, there are a number of different techniques to examine DNA methylation and histone marks -two major epigenetic mechanisms for controlling transcription.…”
Section: Table 1 To Be Inserted Here Methods To Examine the Regulatormentioning
confidence: 99%
“…96 Investigators have also adapted the high-throughput "deep sequencing" techniques used in FGS to the transcriptome, identifying novel isoforms and alternative splice variants, suggesting that 92% of genes may undergo alternative splicing. 82 Capitalizing on these data, more sophisticated microarrays are being developed that will allow researchers to discriminate between isoforms and quantify alternative splicing. 97,98 At the level of the proteome, the most basic question is whether or not a protein is present within a cell or in a comparison of cell lysates.…”
Section: Table 1 To Be Inserted Here Methods To Examine the Regulatormentioning
confidence: 99%